Magnetic Properties Regulation of FeGa and FeGaNi Films with Oblique Magnetron Sputtering - Chun Wang; Sanmin Ke; Zhen Wang (Magnetochemistry, 2022)
Magnetic FeGa and FeGaNi films with an in-plane anisotropy were deposited by employing oblique magnetron sputtering. With the increase in oblique angle, the crystallite size of FeGa decreases, which indicates that oblique sputtering can refine the crystallite size. The remanence ratio of FeGa films increases from 0.5 to 0.92 for an easy axis, and the coercivity increases with the decrease in the crystallite size. The calculated static anisotropic field shows that the in-plane magnetic anisotropy can be induced by oblique sputtering and the strength increases with the oblique sputtering angle. After doping Ni by co-sputtering, FeGaNi films exhibit a stable remanence ratio at 0.8, low coercivity and good anisotropy. With the low sputtering power of the Ni target, there is a competitive relationship between the effect of crystallite size and Ni doping which causes the coercivity of FeGaNi films to first increase and then decrease with the increase in the oblique angle. The FeGaNi film also shows high anisotropy in a small oblique angle. The variation of coercivity and anisotropy of FeGaNi films can be explained by the crystalline size effect and increase in Ni content. For the increasing intensity of collisions between FeGa and Ni atoms in the co-sputtering, the in-plane magnetic anisotropy increases first and then decreases. As a result, the magnetic properties of FeGa films were examined to tailor their magnetic softness and magnetic anisotropy by controlling the oblique sputtering angle and Ni doping.